The profit rate in Chile: 1900-2010 - Diego Polanco (University of Massachusetts, Department of Economics, 2019)
The interest of this paper is to discuss the main features that characterize the accumulation regimes that have taken place during the twentieth century in Chile. Understanding that a set of institutionalized compromises and political con icts are inherent to any capitalist society, I rely on the body of literature of Marxist political economy, which focuses on the dynamics of profitability to describe its reproductive patterns. In light of this analysis, I argue that the main institutional transformations in Chilean history are better understood. I characterize long-waves of capitalist accumulation as accumulation regimes and identify three stages: early expansion, late expansion, and crisis. Using decomposition analysis, I identify recurrent patterns in each phase and also argue that the distributional con ict is historically contingent. Moreover, I implement a novel method proposed by Shaikh (2016) to identify the utilization rate, which allows me to discuss issues of aggregate demand in the decomposition analysis more accurately. Furthermore, I also discuss the relation of the process of urbanization with technical change relying on the Okishio-Marx debate. Finally, I argue that unlike previous accumulation regimes, the neoliberal period relies on reproductive patterns of profitability that makes it highly stable.
Keywords: B51; B52; E11; 330; Profit Rate; Accumulation Regimes; Economic Growth